Exploratory factor analysis (EFA) and reliability analysis of financial literacy among workers - Mohd Hassan, Norsilawati; Ab Rani, Nor Zuriati Amani; Zahari, Nor Sabrina; Nik Hassan, Nik Suriati; Azizan, Nurul Hafizah (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the validity and reliability of financial literacy constructs among workers by employing Exploratory Factor Analysis (EFA) on data collected through a 15-item questionnaire measured using a 5-point Likert scale. A pilot study was conducted with 53 respondents, deemed sufficient based on previous literature. EFA results identified three core dimensions of financial literacy like financial behaviour, financial attitude, and financial knowledge, which collectively accounted for 68.75% of the total variance. It indicate a strong construct validity. All items demonstrated factor loadings above 0.50 and were retained. Reliability analysis using Cronbach's alpha confirmed high internal consistency across all components, with values ranging from 0.735 to 0.908. The findings establish a robust and valid measurement tool for assessing financial literacy among workers and provide a foundational framework for future research and policy interventions aimed at enhancing financial literacy, education and well-being in the workforce for a variety sector.